Fecal microbiome change in patients with ulcerative colitis after fecal microbiota transplantation - A. Y. Tikunov; V. V. Morozov; A. N. Shvalov; A. V. Bardasheva; E. V. Shrayner; O. A. Maksimova; I. O. Voloshina; V. V. Morozova; V. V. Vlasov; N. V. Tikunova (Вавиловский журнал генетики и селекции)
Intestinal human microbiota is a dynamic system that is under the pressures of its host organism and external factors. Microbiota disruption caused by these factors can lead to severe diseases including inflammatory and oncological diseases of the gastrointestinal tract. One of the possible approaches in managing the intestinal microbiota is fecal microbiota transplantation (FT) – transfer of the microbiota from the stool of a healthy donor to the intestinal tract of a recipient patient. Currently, this procedure is recognized as an efficacious method to normalize the intestinal microbiota mainly in inflammatory diseases of the gastrointestinal tract. In Russia, pilot studies of the effectiveness of FT in patients with ulcerative colitis have been conducted for several years, and these studies were started in Novosibirsk. The aim of this study was to assess the change of intestinal microbiome in 20 patients with ulcerative colitis after a single FT procedure. The main method is a comparative analysis of 16S ribosomal RNA sequence libraries constructed using fecal samples obtained from patients with ulcerative colitis before and after FT and sequenced on the Illumina MiSeq platform. The obtained results showed that FT led to an increase in average biodiversity in samples after FT compared to samples before FT; however, the difference was not significant. In the samples studied, the proportion of Firmicutes sequences, the major gastrointestinal microbiota of healthy people, was decreased (~32 % vs. >70 %), while the proportion of Proteobacteria sequences was increased (>9 % vs. <5 %). In some samples collected before FT, sequences of pathogenic Firmicutes and Proteobacteria were detected, including Acinetobacter spp., Enterococcusspp., Klebsiella pneumoniae, Proteus mirabilis, Staphylococcus aureus, Stenotrophomonas maltophylia, Streptococcusspp. In most cases, the proportion of such sequences after FT substantially decreased in appropriate samples. The exception was the Clostridiumdifficilesequences, which accounted for <0.5 % of the sequences in samples from almost half of the patients and after FT, the share of such C. difficilesequences was significantly reduced only in samples from three patients. It should be noted that the proportion of Lactobacillusspp. increased ten-fold and their species composition significantly expanded. According to the obtained results, a preliminary conclusion can be made that even a single FT procedure can lead to an increase in the biodiversity of the gastrointestinal microbiota in patients and to the optimization of the taxonomic composition of the microbiota.